2017
DOI: 10.12659/ajcr.903507
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone-Induced Hemolytic Anemia in a Jehovah’s Witness

Abstract: Patient: Female, 65Final Diagnosis: Ceftriaxone induced immune hemolytic anemiaSymptoms: Blindness • fatigueMedication: —Clinical Procedure: —Specialty: HematologyObjective:Unusual clinical courseBackground:Drug-induced immune hemolytic anemia (DIIHA) is a rare condition that may result from the administration of an antibiotic, most notably the cephalosporin class, commonly used in both the adult and pediatric populations. A delay in recognition by a provider may lead to continuation of the offending agent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The etiology of the symptoms was suspected to be a hemolytic anemia directly related to her ceftriaxone infusions. [ 7 ] De Wilde et al . reported life-threatening ceftriaxone-induced immune hemolytic anemia with an acute kidney injury in a 76-year-old woman,[ 8 ] while Mulkens et al .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of the symptoms was suspected to be a hemolytic anemia directly related to her ceftriaxone infusions. [ 7 ] De Wilde et al . reported life-threatening ceftriaxone-induced immune hemolytic anemia with an acute kidney injury in a 76-year-old woman,[ 8 ] while Mulkens et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a case of ceftriaxone-induced IHA was reported with a patient refusing transfusions for religious reasons (Jehova’s witness). In this case the patient could be stabilized with daily application of erythropoietin, ferrous sulfate, folic acid and vitamin B12 [ 26 ]. In many cases, patients are given steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, recent study reported ceftriaxone-induced neurotoxicity in patients with end-stage renal disease resulting from the delayed clearance of the drug (Inoue and others 2017). In rare cases, ceftriaxone can cause drug-induced hemolytic anemia (Tasch & Gonzalez-Zayaz 2017).…”
Section: Ceftriaxone: β-Lactam Antibioticmentioning
confidence: 99%